Academic (Under)achievement of Intellectually Gifted Students in the Transition Between Primary and Secondary Education: An Individual Learner Perspective - Barbier, Katelijne; Donche, Vincent; Verschueren, Karine (Frontiers in Psychology, 2019)
In the last decade, the Achievement Orientation Model (AOM) of Siegle and McCoach has often been used to quantitatively explore different pathways for academic achievement among intellectually gifted students in educational settings, mostly in secondary education. To study the dynamics of the different components in the AOM, we further examined the inhibiting and facilitating factors associated with academic achievement as experienced by well-performing and underperforming gifted students. Because the transition from elementary to secondary education is a crucial phase for intellectually gifted students, we selected students from the 7th and 8th grade, using purposive sampling. Six gifted students, three well-performing and three underperforming, from two different high schools participated in in-depth interviews. By capturing the lived experiences of six intellectually gifted students in this study, we were able to get more insight into the complex processes that relate to students’ (dis)engagement and (under)achievement in school. The findings underline the value of the AOM and stress the importance of taking learner perceptions into account.